Formation of National Self-Consciousness of Future Music Art Teachers in «Choral Class» - Sokolova, Alla (Professional Art Education, 2020)
Object. The article addresses issues of educating future music teachers, the formation of their national worldview, in which professional knowledge and professional responsibility are formed, are of great importance. The leading role in this direction belongs to the discipline “Choral Class” and the widespread use of choral works written in poetry by Taras Shevchenko. Methods. Traditional historical and pedagogical research methods were used in the work: analytical, historical, and comparative, retrospective, comparative analysis of scientific and pedagogical literature, educational materials. Results. It was revealed that the literary works of Taras Shevchenko were interpreted in their choral works by such famous Ukrainian composers as M. Verbitsky, L. Dychko, M. Karminsky, A. KosAnatolsky, O. Kosits, M. Lysenko, S. Lyudkevich, L. Revutsky, K. Stetsenko, A. Shtogarenko and others. This is since choral music is precisely the spiritual center that for centuries has kept the “genetic code” of Ukrainian culture. The work of the great poet T. Shevchenko has not lost its relevance today. He is dear to us with a word that does not die and exalts the beauty of the Ukrainian nation, awakens the best human feelings, encourages friendship and creative cooperation around the world, teaches us to love Ukraine. Given this, a significant role in the national education of future music teachers is played by the development of choral works by Ukrainian composers based on poems by Taras Shevchenko in the classes of the “Choir Class”. Studying the works of A. Kos-Anatolsky, Y. Stepova, A. Shtogarenko and others, written in poems by T. Shevchenko, in the classes of the «Choir Clas»”, students can not only understand the social significance of the feelings of both the poet and composers, but also experience that or other artistic image. This contributes to the development of the personal emotional sphere of students, their spirituality, reflection. Conclusions. Mastering the above compositions teaches future music teachers how pure and honest, humane and truthful, hardworking and sociable, full of self-worth and respect for all who work, a real person should be. Taras Shevchenko’s сreativity, increased by the skill of Ukrainian composers, brings to young people the educational potential aimed at educating the national consciousness, educating patriotism of national dignity, spiritual enrichment of the individual.
Keywords: national education; Taras Shevchenko; choral works; Ukrainian composers; future teachers of musical art